Comparative study of crystallization, semicrystalline morphology, and molecular mobility in nanocomposites based on polylactide and various inclusions at low filler loadings. (5th March 2021) - Papadopoulos, Lazaros; Klonos, Panagiotis A.; Terzopoulou, Zoi; Psochia, Eleni; Sanusi, Olawale Monsur; Hocine, Nourredine Aït; Benelfellah, Abdelkibir; Giliopoulos, Dimitrios; Triantafyllidis, Konstantinos; Kyritsis, Apostolos; Bikiaris, Dimitrios N.
Abstract: In this article, we report effects imposed to polylactide (PLA) by fillers of different geometries and surface chemistry, namely mesoporous silicas, carbon nanotubes (CNT), mixtures of CNT and clays as well as new hybrid particle of the latter two, at low loadings (0.5–5 wt%). The initial scope for the nanocomposites preparation is the improvement of the rate of crystallization, being extremely slow in neat PLA and the study of structure - semicrystalline morphology - molecular mobility relationship. To that aim, Fourier transform infra red (FTIR) spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry (DSC), polarized optical microscopy (POM) and broadband dielectric spectroscopy (BDS) were employed and evaluated by widely used analysis routes. All nanofillers were found to offer crystallization sites accelerating crystallization. The effect is systematically stronger for the silicas than the CNT-based fillers; moreover, was found to correlate with the weaker and stronger disturbance of the PLA carbonyls (FTIR), respectively, due to interfacial interactions. Comparing to clay/CNT mixture, the hybrid clay/CNT and neat CNTs were found more effective in improving the crystallization rate. Despite the crystallization rate improvement, the degree of crystallinity was not enhanced. Significant alternations in the semicrystalline morphology were recorded in the nanocomposites by POM. Regarding the main results on molecular mobility (DSC, BDS), a slight deceleration of segmental dynamics (glass transition, α relaxation) was recorded in the nanocomposites, accompanied by an increase in cooperativity. In general, results suggest complex phenomena affecting segmental dynamics, for example constraints imposed by the filler attractions (FTIR, DSC) and spatial confinement effects on the amorphous polymer between the fillers or crystals, that tend to decelerate and accelerate the dynamics, respectively. BDS enabled the recording of an additional clay-induced relaxation in the nanocomposites that shows cooperative characteristics and a quite high strength, most possibly arising from the interfacial polymer. Despite the lack of microscopy measurements for morphology, the combined data showed indirect although strong indications for the best dispersion in the PLA matrix at 1 wt% particle loading, independently from the type of the filler. Graphical abstract: Image 1 Highlights: PLA nanocomposites reinforced by mesoporous silicas, CNTs, clays (MMT) and hybrid MMT/CNT. Investigation employing structural (FTIR, XRD, POM), thermal (DSC) and dielectric (BDS) methods. Evaluation of filler polymer interfacial interactions and rigid amorphous fraction (RAF). Effects on crystalline rate and fraction, as well as semicrystalline morphology. Molecular dynamics mapping – local, segmental and filler induced dynamics.